The Influence of Crude Oil Prices Volatility, the Internet and Exchange Rate on the Number of Foreign Tourist Arrivals in Indonesia - Millia, Heppi; Adam, Pasrun; Saenong, Zainuddin; Balaka, Muh. Yani; Pasrun, Yuwanda Purnamasari; Saidi, La Ode; Rumbia, Wali Aya (International Journal of Energy Economics and Policy, 2020)
This paper seeks to examine the influence of crude oil prices volatility, the internet, and exchange rate on the number of foreign tourist arrivals in Indonesia. Using a time-series dataset from 1995 to 2018 and employing an autoregressive distributed lag (ARDL) model plus an error correction model (ECM-ARDL), our research shows that in the long run, the internet has a positive influence on the number of foreign tourist arrivals. Every 1% rise in the internet, the number of foreign tourist arrivals rises by 0.49%. However, crude oil prices volatility and exchange rates do not significantly affect the number of foreign tourist arrivals. In the short run, there is a negative influence of crude oil price volatility on the number of foreign tourist arrivals. Meanwhile, the exchange rate positively affects the number of foreign tourist arrivals, meaning that the appreciation (depreciation) of the IDR exchange rate against the USD causes the number of foreign tourist arrivals to go down (up). Keywords: Crude oil price volatility, the internet, exchange rate, foreign tourist arrivals, ARDL model. JEL Classifications: C32, E310, F310, O330 DOI: https://doi.org/10.32479/ijeep.10083